Analysis of Cyber Public Relations Strategy for Dealing with Hate Speech on Instagram @indonesiabaik.id in Maintaining Reputation - Anggraeni, Catharina Sylvi; Hartanti, Lisa Esti Puji (JURNAL KOMUNIKASI INDONESIA, 2025)
This study examines the cyber public relations strategies employed by the Indonesian Ministry of Communication and Digital in addressing hate speech on the Instagram account @indonesiabaik.id, aiming to maintain the brand’s reputation among younger audience. Despite the government’s efforts to provide interactive, creative, and relevant content, the account often faces unfavorable reactions due to a perceived gap between the presented content and societal realities. This research aims to analyze the cyber public relations strategy for dealing with hate speech on Instagram @indonesiabaik.id to maintain a reputation. Using concepts of hate speech, public relations, issue management and reputation, this research applies a descriptive qualitative approach, incorporating interviews and document analysis. This study presents three key findings. First, grouping negative comments on social media remains a challenge for government brands. Second, responsive digital public relations strategies involve general process including fact-finding, planning, action, communication, and evaluation, along with specific measure in managing communication messages through identifying issues, analyzing issues, formulating an issue, implementing the program, and conducting evaluation. Third, reputation management on social media hinges on communication strategies that prioritize credibility, reliability, trustworthy, and responsibility. This study has implications for the development of cyber public relations strategies on social media, particularly for the @indonesiabaik.id account, in dealing with hate speech to protect its reputation, which benefits the sustainability of organizations.